La evaluación formativa en el proceso de enseñanza aprendizaje de la asignatura de Matemática en Educación General Básica Superior - Medina Díaz, Valeria Stefania (2024)
Formative evaluation as a process is focused on the improvement of educational quality; this research analyzed its contribution to the teaching-learning process of Mathematics in the eighth grade of Higher General Basic Education at the “Colegio de Bachillerato 27 de Febrero”. Therefore, the research had a mixed approach with a descriptive scope, with a documentary and field design; the method of bibliographic review with indexing technique and the application of instruments such as search log, bibliographic and content files, allowed describing the conceptual categories to contrast them with the empirical information, compiled by means of documentary analysis record cards and surveys. The results showed that the evaluation is developed in a continuous and progressive way and provides information on the development of the teaching-learning process; however, it was detected as a weakness that there is little participation, constructive feedback and diversity of techniques and instruments, hindering the adequate execution of the formative evaluation. Consequently, it is concluded that its contribution to the teaching-learning process is limited. Keywords: evaluation, formative evaluation, constructive feedback, learning, educational quality.